Formal [5+3] Cycloaddition between Isatin-Based α-(Trifluoromethyl)imine Ylides and Vinyloxiranes: Diastereoselective Access to Medium-Heterocycle-Fused Spirooxindoles - Zhao, Hong-Wu; Wang, Li-Ru; Ding, Wan-Qiu; Guo, Jia-Ming; Tang, Zhe; Song, Xiu-Qing; Wu, Hui-Hui; Fan, Xiao-Zu; Bi, Xiao-Fan; Zhong, Qi-Di (Synlett, 2020)
In the presence of Pd2(dba)3·CHCl3 (2.5 mol%), PPh3 (10 mol%), and 60% NaH (1.5 equiv), the formal [5+3] cycloaddition between isatin-based α-(trifluoromethyl)imines and vinyloxiranes proceeded readily in 1,2-DCE at 40 ℃ and afforded cis-configured medium-heterocycle-fused spirooxindoles in the reasonable chemical yields with >20:1 dr. The relative stereochemical configuration of the title products was identified by X-ray diffraction analysis.
Keywords: [5+3] cycloaddition; isatin-based α-(trifluoromethyl)imine; vinyloxirane; spirooxindole; diastereoselectivity